2009
DOI: 10.1007/s12010-009-8821-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fungi and Gram-Negative Bacteria by Bacteriocin BacTN635 Produced by Lactobacillus plantarum sp. TN635

Abstract: The aim of this study was to evaluate 54 lactic acid bacteria (LAB) strains isolated from meat, fermented vegetables and dairy products for their capacity to produce antimicrobial activities against several bacteria and fungi. The strain designed TN635 has been selected for advanced studies. The supernatant culture of this strain inhibits the growth of all tested pathogenic including the four Gram-negative bacteria (Salmonella enterica ATCC43972, Pseudomonas aeruginosa ATCC 49189, Hafnia sp. and Serratia sp.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 28 publications
3
59
0
5
Order By: Relevance
“…The highest antibacterial activity (inhibition zones of >12.00 mm) was achieved by 6.6, 3.5, 4.3, 3.2, and 2.6% of L. plantarum isolates against E. coli, Salmonella typhimurium, Shigella flexneri, Staphylococcus aureus, and L. monocytogenes, respectively. This is in line with the study of Smaoui et al (2010) who found that only one isolate of L. plantarum (TN635) out of 54 isolates evaluated showed significant levels of inhibitory activities against four Gram-negative pathogenic bacteria (Salmonella enterica, Pseudomonas aeruginosa, Hafnia sp., and Serratia sp.). Based on these results, nine isolates could be identified as having broad and effective antibacterial activity against four (IMAU70095 and IMAU50045) or all five of the indicator bacteria (IMAU80106, IMAU10996, IMAU10216, IMAU70023, IMAU30043, IMAU30162, and IMAU10256) (Supplementary Table 1).…”
Section: Initial Screening For Antibacterial Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…The highest antibacterial activity (inhibition zones of >12.00 mm) was achieved by 6.6, 3.5, 4.3, 3.2, and 2.6% of L. plantarum isolates against E. coli, Salmonella typhimurium, Shigella flexneri, Staphylococcus aureus, and L. monocytogenes, respectively. This is in line with the study of Smaoui et al (2010) who found that only one isolate of L. plantarum (TN635) out of 54 isolates evaluated showed significant levels of inhibitory activities against four Gram-negative pathogenic bacteria (Salmonella enterica, Pseudomonas aeruginosa, Hafnia sp., and Serratia sp.). Based on these results, nine isolates could be identified as having broad and effective antibacterial activity against four (IMAU70095 and IMAU50045) or all five of the indicator bacteria (IMAU80106, IMAU10996, IMAU10216, IMAU70023, IMAU30043, IMAU30162, and IMAU10256) (Supplementary Table 1).…”
Section: Initial Screening For Antibacterial Activitysupporting
confidence: 90%
“…In addition, the use of chemical preservatives in food production has been significantly reduced recently, due to increased public awareness of the health concerns associated with them. The addition of natural biopreservatives, such as isolates of lactic acid bacteria (LAB) with antibacterial activity, is one potential strategy to both improve food quality and extend shelf life (Smaoui et al 2010). However, the practical application of such an approach does suffer from technical problems such as incompatibility with the taste of food and loss of antimicrobial activity during food digestion (Gálvez et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supernatant of L. plantarum TN635 strain inhibited the growth of all used indicator microorganisms, among which E. coli ATCC8739 (SMAOUI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) as bio-preservation organisms play a key role in food fermentations where they not only contribute to the development of desired sensory properties in the final product but also to their microbiological safety (Smaoui et al 2010;Cizeikiene et al 2013). The antimicrobial effect of LAB is related to the production of organic acids, short chain fatty acids, hydrogen peroxide and proteinaceous compounds -bacteriocins and bacteriocin-like inhibitory substances (BLIS) (Dalié et al 2010).…”
Section: Introductionmentioning
confidence: 99%